An in-depth study of substrate effect on the performance of BOD sensor type microbial fuel cell - Thi My Linh, Nguyen; The Hai, Pham (Vietnam Journal of Biotechnology, 2022)
Nowadays, instant assessment of the organic content in wastewater is an urgent requirement to reduce water pollution. Microbial fuel cells (MFCs) can be used as effective biosensors for rapidly measuring BOD concentration of wastewater. However, wastewaters from different sources may consist of diverse chemical components, which may affect the BOD-measuring performance of MFC-type biosensors. Therefore, in this research, we tested different input substrates for the BOD sensor type MFC (MFC_BOD) to investigate their effects on the performance of the MFC. The substrates belonging to diverse groups such as carbohydrates, organic acids, amino acids and some chlorinated compounds (xenobiotics) were tested at different concentrations equivalent to BOD levels from 10 to 200 mg L-1. Concurrently, we also analyzed the alteration of the bacterial community in the anode of the MFC when tested with those different substrates by using PCR-DGGE. Our results showed that the MFC_BOD could have linear current-to-BOD responses (with the respective R2 values >0.9) to more metabolizable substrates such as carbohydrates, organic acid and glycerol; while it responded less sensitively at different degrees to some amino acids (serine, threonine and methionine) and did not respond to chloroform and chlorobenzene (chlorinated compounds). PCA and bacterial community analysis results surprisingly imply that such different responses may be solely due to different bio(electro)chemical processes associated with the substrates but not due to changes in the composition of the bacterial community. The results suggest that, to enable the MFC_BOD to accurately sense the BODs of the wastewaters containing recalcitrant or toxic substrates, special procedures are required to enrich in the anode the bacterial communities acclimated to the substrates right from the beginning